1999
DOI: 10.1038/8737
|View full text |Cite
|
Sign up to set email alerts
|

A radiation hybrid map of the rat genome containing 5,255 markers

Abstract: A whole-genome radiation hybrid (RH) panel was used to construct a high-resolution map of the rat genome based on microsatellite and gene markers. These include 3,019 new microsatellite markers described here for the first time and 1,714 microsatellite markers with known genetic locations, allowing comparison and integration of maps from different sources. A robust RH framework map containing 1,030 positions ordered with odds of at least 1,000:1 has been defined as a tool for mapping these markers, and for fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
207
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(214 citation statements)
references
References 43 publications
6
207
0
1
Order By: Relevance
“…Similar clustering of SSR markers was also reported in the tomato (Broun and Tanksley 1996;Areshchenkova and Ganal 1999) and rice linkage maps (McCouch et al 2003). Physical clustering of SSR markers was also reported in the rat radiation hybrid map (Watanabe et al 1999) and in barley . Morgante et al (2002) and Cardle et al (2000) indicated that microsatellites are significantly associated with the low-copy fraction of plant genomes based on the estimation of microsatellite density in Arabidopsis thaliana, rice, soybean, maize, and wheat.…”
Section: Discussionmentioning
confidence: 67%
“…Similar clustering of SSR markers was also reported in the tomato (Broun and Tanksley 1996;Areshchenkova and Ganal 1999) and rice linkage maps (McCouch et al 2003). Physical clustering of SSR markers was also reported in the rat radiation hybrid map (Watanabe et al 1999) and in barley . Morgante et al (2002) and Cardle et al (2000) indicated that microsatellites are significantly associated with the low-copy fraction of plant genomes based on the estimation of microsatellite density in Arabidopsis thaliana, rice, soybean, maize, and wheat.…”
Section: Discussionmentioning
confidence: 67%
“…Statistical analyses show significant differences in astrogliosis and myelination defects between the 2 species ( * , P Ͻ 0.05 and *** , P Ͻ 0.001). mouse, and human genomes encode similar numbers of genes (19)(20)(21)(22)(23). Therefore, we suggest that differences in genetic background between mice and rats may be one possible explanation for the neuroprotective effect of hypoxia in mice but not in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the polymorphic nature of Ncl Z1 has been previously used in genetic mapping, and it is known as marker D9Arb5 on rat chromosome 9 (29). Many of the polymorphic dinucleotide repeats used in genetic mapping consist of alternating purine͞pyrimidine repeats and thus have the potential to form Z-DNA.…”
Section: Discussionmentioning
confidence: 99%